Evidence of an environmental effect on survival in ALS. Issue 7 (December 2014) - Keren, Noa; Scott, Kirsten M.; Tsuda, Miho; Barnwell, Jessica; Knibb, Jonathan A.; Ellis, Cathy M.; Leigh, P. Nigel; Shaw, Christopher E.; Al-Chalabi, Ammar
Abstract Amyotrophic lateral sclerosis (ALS, motor neuron disease) is a neurodegenerative disorder of motor neurons leading to paralysis and eventual death by respiratory failure. Median survival is 2–3 years. Susceptibility genes, environmental triggers and disease related prognostic factors have been established, but environmental effects on survival are yet to be investigated. We analysed survival in the South-East England ALS register (SEALS register). Kaplan-Meier and Cox regression analyses were used to investigate survival in London, coastal and rural areas according to postcode at diagnosis. Results showed that there were 933 cases of ALS identified in the catchment area during the study period (1994–January 2012). Cox regression demonstrated a highly significant model for survival with significant protective variables: coastal residency, riluzole use and younger age at onset. Significantly worse survival was associated with London residency, older age as well as definite and probable El Escorial classifications. In conclusion, these findings suggest the possibility of an environmental effect on survival in ALS.